Bildungspotenziale der Olympischen Idee - Pietsch, Stefanie (1. Auflage 2021, 2021)
The Olympic Idea moves almost permanently between idealized and uncritical enthusiasm on the one hand and strict, almost hostile rejection on the other. The aim of this work is to take a well-founded look at various aspects of the Olympic reality and to summarize texts on interesting, current and discussion-intensive Olym-pic topics in one volume. The well-founded examination of complex topics, which allows a multifaceted view and the formation of one's own opinion, offers thought-provoking impulses and a basis for discussion for readers from very different target groups (students, lecturers, trainers, athletes, sports enthusiasts).